Prosumers in Action: The Analysis of Social Determinants of Photovoltaic Development and Prosumer Strategies in Poland - Zuk, Piotr; Zuk, Paweł (International Journal of Energy Economics and Policy, 2022)
The aim of this article is to explain the mechanisms that have increased the grassroots development of photovoltaics (PV) in Poland and to explain the motives of prosumers. Micro-installations have become a driving force for PV in Poland, thanks to which the country, whose energy industry is mostly based on hard coal and lignite, became the fourth PV growth market in Europe in 2020. Based on focus group interviews, the authors explain the motives of prosumers, the impact of investing in PV on changing their lifestyle, their readiness to switch to off-grid systems and their potential to create a prosumer social movement in Poland. The decentralisation of the energy sector and the mass prosumer response to the increase in energy price led the government to change the regulations in force in Poland from April 2022, which defined the method of settling the surplus energy given by prosumers to the grid.